High‐quality GaN film and AlGaN/GaN HEMT grown on 4‐inch Si(110) substrates by MOCVD using an ultra‐thin AlN/GaN superlattice interlayer. Issue 5 (29th December 2014) - Shen, X. Q.; Takahashi, T.; Ide, T.; Shimizu, M.
<x xml:space="preserve">Abstract</x> We report the characterization results of GaN films and AlGaN/GaN heterostructure grown on 4‐inch Si(110) substrates by MOCVD using an ultra‐thin AlN/GaN superlattice interlayer (SL IL) structure. The structure optimization of the SL IL, characterizations of the GaN film quality and the strain state are carried out. The SL IL is found to play an important role in controlling the strain states in GaN films. A crack‐free GaN film up to 2 μm thick is achieved by inserting one SL IL. High‐quality GaN is obtained with the FWHM values of (002) and (102) diffraction peaks from a 2 μm‐thick GaN film being as narrow as 427 arcsec and 665 arcsec, respectively. A flat surface morphology of GaN with monolayer steps is obtained. Based on the SL IL technique, AlGaN/GaN heterostructure is grown with 2DEG mobility and sheet carrier density being ∼1500 cm2/Vs and 1.2 × 1013 cm−2. A high‐electron‐mobility transistor (HEMT) is fabricated and good DC characteristics are demonstrated.